2006
DOI: 10.1212/01.wnl.0000244468.22377.6b
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of bacterial strains to clinical syndromes of Campylobacter -associated neuropathies

Abstract: The bacterial findings support the proposal that Guillain-Barré syndrome (GBS) and muscle stretch reflex-preserved GBS comprise a continuous spectrum as well as do Fisher syndrome (FS), FS/GBS overlap, Bickerstaff brainstem encephalitis (BBE), BBE/GBS overlap, acute ophthalmoparesis, ataxic GBS, and acute oropharyngeal palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 35 publications
2
68
0
2
Order By: Relevance
“…65 GD1c-like LOS, which mimics GQ1b, also was identified in C. jejuni isolates from FS. 54,94 GM2/GD2 synthase knockout mice, which lack GQ1b and GT1a, are immune-naive hosts that can be used to obtain high anti-ganglioside antibody responses. Immunization of these mice with C. jejuni (CF93-6) LOS generated monoclonal IgG antibodies that reacted with GQ1b and GT1a.…”
Section: Campylobacter Genes As the Determinant Of Neuropathy Developmentioning
confidence: 99%
See 1 more Smart Citation
“…65 GD1c-like LOS, which mimics GQ1b, also was identified in C. jejuni isolates from FS. 54,94 GM2/GD2 synthase knockout mice, which lack GQ1b and GT1a, are immune-naive hosts that can be used to obtain high anti-ganglioside antibody responses. Immunization of these mice with C. jejuni (CF93-6) LOS generated monoclonal IgG antibodies that reacted with GQ1b and GT1a.…”
Section: Campylobacter Genes As the Determinant Of Neuropathy Developmentioning
confidence: 99%
“…Over a 9-year period, 139 patients were found, from whom C. jejuni had been isolated and who had medical histories available for clinical analysis, 54 even though the latent period between preceding intestinal infection and neuropathy onset often exceeded the excretion period of viable C. jejuni cells in stools. Diagnoses for the other 139 patients were GBS (n ϭ 90, 65%), FS (n ϭ 22, 16%), atypical GBS with preserved muscle stretch reflexes (MSR; n ϭ 10, 7%), FS overlapping GBS (FS/GBS; n ϭ 6, 4%), Bickerstaff's brainstem encephalitis (BBE; n ϭ 1, 0.7%), BBE overlapping GBS (BBE/ GBS; n ϭ 2, 1.4%), acute ophthalmoparesis without ataxia (AO; n ϭ 3, 2.1%), ataxic GBS (n ϭ 1, 0.7%), acute oropharyngeal palsy (n ϭ 3, 2.1%), and chronic inflammatory demyelinating polyneuropathy (CIDP; n ϭ 1, 0.7%).…”
Section: Campylobacter Genes As the Determinant Of Neuropathy Developmentioning
confidence: 99%
“…In most cases the infections are self-limiting; however, in rare cases, some patients with C. jejuni enteritis later develop neurological conditions such as Guillain-Barré or Fisher syndrome (34). Most strains of C. jejuni isolated from patients with various neurological conditions synthesize lipooligosaccharides (LOS) exhibiting molecular mimicry with the carbohydrate moieties of gangliosides enriched in peripheral nerves (20). Ganglioside mimicry by C. jejuni LOS, therefore, could induce the production of autoantibodies against gangliosides and the development of neurological disease (36).…”
mentioning
confidence: 99%
“…15 Immunological studies have shown that some patients develop MFS after Campylobacter jejuni infection, including those with GBS/MFS overlap. 16,17 These findings suggest that AMAN and MFS are part of the same spectrum of disease. In our study, facial weakness was more common in AIDP than MFS or AMAN, whereas delayed facial weakness occurred at the same frequency in AIDP, AMAN, and MFS.…”
Section: Discussionmentioning
confidence: 79%